2020
DOI: 10.3389/fpubh.2020.00086
|View full text |Cite
|
Sign up to set email alerts
|

Identification of High-Risk Pregnancies in a Remote Setting Using Ambulatory Blood Pressure: The MINDI Cohort

Abstract: Conclusion: MINDI were bi-directionally associated with blood pressure indicators. In this MINDI cohort, infections, nutrients and cytokines both raised, and lowered BP indices. The presence of eMAP identified pregnant women at risk of hypertension whereas low PP was associated with lower SFH. Therefore, MAP and PP may help in detecting women at risk of adverse pregnancy outcomes in settings with limited access to technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 94 publications
2
12
0
2
Order By: Relevance
“…In this population of pregnant mothers with low plasma volumes we found a consistent association of hepcidin with lower urinary pH, another indicator of volemic status ( 51 ), suggesting that hemoconcentration, previously reported in this population ( 25 ), may contribute to higher hepcidin concentrations.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In this population of pregnant mothers with low plasma volumes we found a consistent association of hepcidin with lower urinary pH, another indicator of volemic status ( 51 ), suggesting that hemoconcentration, previously reported in this population ( 25 ), may contribute to higher hepcidin concentrations.…”
Section: Discussionsupporting
confidence: 82%
“…Gray arrows with positive (+) and negative (–) signs indicate positive and negative associations, respectively. Associations of pulse pressure with TNF-α ( 25 ) and of CRP with wood smoke ( 24 ) had been reported previously. Black arrows with positive and negative signs inside black circles indicate factors that increased or decreased the odds of SFH between the 10th and the 90th centiles (SFH 10–90), between the 3rd and 10th centiles (SFH 30–10), and of <3rd centile using the INTERGROWTH-21 standards, and the odds of SFH <10th centile using the CLAP standards.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Interestingly, the continuous variables for DBP and MAP, as well as iron supplementation were positively associated with SFH Z-score, but were not associated with sonography-estimated fetal weight or AFI. Supporting our findings, there is evidence that lower SFH Z-scores are associated with lower pulse pressure in a vulnerable indigenous population ( 53 ). Given the complexity of the SFH measurement, associations of blood pressure measurements with SFH warrant further investigation.…”
Section: Discussionsupporting
confidence: 87%
“…We found that the diastolic blood pressure in the HCA group was significantly lower than that in the non-HCA group, and diastolic blood pressure was an independent protective factor in the complex model. Recent studies have suggested that infections related to anti-inflammatory reactions will lead to a reduction in diastolic blood pressure [ 35 ]. Compared to the babies born after idiopathic premature delivery or PROM, the babies born from hypertensive mothers have a lower risk of brain damage [ 36 ].…”
Section: Discussionmentioning
confidence: 99%